Occupational stress and the laws in selected jurisdictions - Ali Mohamed, Ashgar Ali; Eishan Jan, Mohammad Naqib; Ahmad, Muhamad Hassan; Hussain, Shahadat (The Turkish Online Journal of Design, Art and Communication, 2018)
In the contemporary modern and globalised world, it is common for the majority of employers to draw a great attention to the productivity of the workforce rather than the employees working capability and physical and mental conditions. Businesses and industries have always been striving towards maximising profit and minimising the cost. As a result, employees of uncountable organisations suffer from the alarming occupational stress in catching up with the respective schedule of productions, shipments and services. The question arises here is that whether there should be some regulatory measures to relief the occupational stress of the workforce? Accordingly, this article examines the laws relating to the occupational safety and health in selected jurisdictions, namely, Malaysia, Australia, Canada, the United Kingdom and New Zealand in order to evaluate whether these laws protect workers’ mental health. It is found that the existing legislations on occupational health and safety in the selected jurisdictions do not explicitly address on the emotional and mental health of employees. Therefore, authors propose that a specific legislation is warranted to regulate occupational stress closely and carefully in order to provide better work-life balance to the workforce.